ChemInform Abstract: Dual Selectivity: Electrophile and Nucleophile Selective Cross‐Coupling Reactions on a Single Aromatic Substrate. Issue 6 (11th February 2014) - Heinrich, Annika C. J.; Thiedemann, Birk; Gates, Paul J.; Staubitz, Anne
Abstract The first microwave assisted very high selective one‐pot Stille cross‐coupling of aromatic compounds yields bifunctional products.